2021
DOI: 10.3390/ph14020135
|View full text |Cite
|
Sign up to set email alerts
|

Ameliorative Effects of Loganin on Arthritis in Chondrocytes and Destabilization of the Medial Meniscus-Induced Animal Model

Abstract: Arthritis is a common inflammatory disease that causes pain, stiffness, and joint swelling. Here, we investigated the ameliorative effects of loganin on arthritis in vitro and in vivo. A single bioactive compound was fractionated and isolated from Cornus officinalis (CO) extract to screen for anti-arthritic effects. A single component, loganin, was identified as a candidate. The CO extract and loganin inhibited the expression of factors associated with cartilage degradation, such as cyclooxygenase-2 (COX-2), m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 40 publications
1
6
0
Order By: Relevance
“…On the other hand, the higher dose of the extract reduces the occurrence of the factors generating an increase in the level of metalloproteinases, i.e., oxidative stress or inflammation, thus demonstrating a beneficial effect on the development and stability of atherosclerotic lesions resulting from a diet rich in cholesterol. Most of the studies conducted so far on the impact of the extract or active compounds obtained from the genus Cornus on metalloproteinases mainly concern MMP-3 and MMP-13 [ 34 , 35 , 36 , 37 ], and a diminution in the expression of these enzymes was also observed; ergo, our results are consistent with the earlier outcomes, concomitantly expanding the knowledge on this subject.…”
Section: Discussionsupporting
confidence: 90%
“…On the other hand, the higher dose of the extract reduces the occurrence of the factors generating an increase in the level of metalloproteinases, i.e., oxidative stress or inflammation, thus demonstrating a beneficial effect on the development and stability of atherosclerotic lesions resulting from a diet rich in cholesterol. Most of the studies conducted so far on the impact of the extract or active compounds obtained from the genus Cornus on metalloproteinases mainly concern MMP-3 and MMP-13 [ 34 , 35 , 36 , 37 ], and a diminution in the expression of these enzymes was also observed; ergo, our results are consistent with the earlier outcomes, concomitantly expanding the knowledge on this subject.…”
Section: Discussionsupporting
confidence: 90%
“…Using destabilization of the medial meniscus (DMM)-induced OA mice as a model, loganin delayed the development of OA, and attenuated cartilage matrix catabolism and pyroptosis of chondrocytes in articular cartilage.Yang et al showed that loganin inhibited the level of apoptosis, decreased the release of catabolic enzymes and the degradation of ECM in IL-1β-treated chondrocytes, and in vivo experiments of OA rats, it has also been confirmed that loganin can inhibit cartilage degradation and cell apoptosis(Yang et al, 2019). The antiinflammatory effects and mechanisms of loganin on IL-1β-induced arthritis model in chondrocyte and DMM-induced mouse model were also investigated by Park et al The results also showed that loganin had a protective effect on arthritis(Park et al, 2021).The inflammatory response of arthritis is mainly dependent on the NF-κB and PI3K/Akt signaling pathways. A recent mechanistic study showed that loganin treatment inhibited the nuclear translocation of p65 protein and decreased the amount of p-IκB in chondrocytes.…”
mentioning
confidence: 80%
“…Yang et al showed that loganin inhibited the level of apoptosis, decreased the release of catabolic enzymes and the degradation of ECM in IL‐1β‐treated chondrocytes, and in vivo experiments of OA rats, it has also been confirmed that loganin can inhibit cartilage degradation and cell apoptosis (Yang et al, 2019). The antiinflammatory effects and mechanisms of loganin on IL‐1β‐induced arthritis model in chondrocyte and DMM‐induced mouse model were also investigated by Park et al The results also showed that loganin had a protective effect on arthritis (Park et al, 2021).…”
Section: Pharmacology Of Loganinmentioning
confidence: 97%
“…Fourteen iridoids 16 , 28 , 31 , 35 , 51 , 70 , 71 , 77 , 78 , 81 , 85 , 92 , 94 and 105 with anti-inflammatory activity have been isolated from the Patrinia genus. The anti-inflammatory activity was mainly screened by cell models [ [16] , [17] , [18] , [19] , [21] , [22] , [28] , [29] , [30] , [53] , [54] , [55] , [58] , [72] , [78] ] and animal models [ [31] , [32] , [33] , [34] , [35] , [36] , [37] , [59] , [60] , [61] , [73] ]. The cell models were RAW264.7 cell and chondrocyte induced by LPS, and the animal models were colitis mice induced by AKI, UC and DSS ( Table 2 ).…”
Section: Active Iridoids and Their Mechanisms In Patrinia ...mentioning
confidence: 99%